Altered aminoacid and lipid metabolism in a rat orofacial inflammation model determined by omics approach: potential role in trigeminal sensitisation - Krisztina Takács-Lovász; Timea Aczél; Violetta Mohos; Máté Harmath; Jennet Pirkuliyeva; Gellért Karvaly; Róbert Farkas; Michal Ciborowski; Joanna Godzien; Kata Bölcskei; József Kun; Zsuzsanna Helyes (The Journal of Headache and Pain)
Abstract Background Trigeminal activation and sensitisation involved in chronic inflammatory orofacial pain share several similarities with headaches, including migraine. Therefore, understanding the pathophysiological mechanisms is important to determine novel therapies, in which animal models are crucial. Here we aimed to identify key mediators, mechanisms and networks using unbiased multi-omic approaches in a rat orofacial inflammatory pain model. Methods Complete Freund’s Adjuvant (CFA, 50 µl, 1 mg/mL) was injected into the right whisker pad of male Wistar rats (n = 5–11/group), mechanonociceptive threshold was measured by von Frey filaments. Plasma concentrations of metabolites were measured both by targeted (MxP Quant 500 kit) and untargeted mass spectrometry methods on day 3 when maximal facial allodynia developed. Next-generation sequencing of the trigeminal ganglia (TG) was performed, furthermore, transcriptomic and plasma metabolomic data were analysed together. Results Plasma carnosine, serotonin and fatty acid levels significantly increased, while tryptophan, kynurenine, tyrosine, phenylalanine, asparagine, glycerolipids, and sphingolipids decreased in response to orofacial inflammation. CFA upregulated the Cxcr3 chemokine receptor and downregulated GNRHR in the TG. Bioinformatic analysis revealed altered amino acid metabolism and fatty acid beta-oxidation involved in mitochondrial energy production, neuroinflammation and immune responses. Conclusions Integrated joint pathway analysis of metabolomic and transcriptomic data provides a useful approach to determine pathophysiological mechanisms of trigeminal sensitization and identify novel drug targets for orofacial pain and headaches.